2007
DOI: 10.1063/1.2778419
|View full text |Cite
|
Sign up to set email alerts
|

Breaking bonds with the left eigenstate completely renormalized coupled-cluster method

Abstract: The recently developed [P. Piecuch and M. Wloch, J. Chem. Phys.123, 224105 (2005)] size-extensive left eigenstate completely renormalized (CR) coupled-cluster (CC) singles (S), doubles (D), and noniterative triples (T) approach, termed CR-CC(2,3) and abbreviated in this paper as CCL, is compared with the full configuration interaction (FCI) method for all possible types of single bond-breaking reactions between C, H, Si, and Cl (except H2) and the H2SiSiH2 double bond-breaking reaction. The CCL method is in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 14 publications
2
65
0
Order By: Relevance
“…Prior work on molecules containing Cu 2 O 2 2+ cores has demonstrated that the CR-CC(2,3) level can predict accurate relative energies for isomers differing significantly in their degree of biradical character. 50,51 Several other benchmark studies and applications have shown that in spite of its single-reference character, the CR-CC(2,3) approach is capable of providing a highly accurate description of the lowest-energy singlet and triplet states of biradicals and systems undergoing significant bond rearrangements, [84][85][86][87][88][89][90][91][92] where the conventional CC methods, such as CCSD and CCSD(T), 93 fail or have considerable problems. On the basis of this positive experience, we regard the CR-CC(2,3) level as a reference level for assessing the accuracy of other methods used in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work on molecules containing Cu 2 O 2 2+ cores has demonstrated that the CR-CC(2,3) level can predict accurate relative energies for isomers differing significantly in their degree of biradical character. 50,51 Several other benchmark studies and applications have shown that in spite of its single-reference character, the CR-CC(2,3) approach is capable of providing a highly accurate description of the lowest-energy singlet and triplet states of biradicals and systems undergoing significant bond rearrangements, [84][85][86][87][88][89][90][91][92] where the conventional CC methods, such as CCSD and CCSD(T), 93 fail or have considerable problems. On the basis of this positive experience, we regard the CR-CC(2,3) level as a reference level for assessing the accuracy of other methods used in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…31 The CCL method belongs to a larger CR-CC(m, n) family based on the biorthogonal formulation 29,30 of the method of moments coupled-cluster equations. [32][33][34][35] CCL has been shown to reproduce full configuration interaction (FCI) PESs with small errors for the single-bond-breaking reactions of nine closed-shell C-H-Si-Cl molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] CCL has been shown to reproduce full configuration interaction (FCI) PESs with small errors for the single-bond-breaking reactions of nine closed-shell C-H-Si-Cl molecules. [29][30][31] The restricted open-shell CCL (ROCCL) method has been shown to properly break the OH and F 2 + bonds within reasonable accuracy. 28 The nonparallelity errors (NPE, defined 28 as the difference between the most positive and most negative signed errors along a given a The MRCI(Q) numbers are not available for H2Si-Cl due to CASSCF convergence problems in the R(Si-Cl) ) 3.4-6.8 Å region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is abbreviated as CR-CCL and is appropriately described by Piecuch(Piecuch et al, 2002) and Ge (Ge et al, 2007). …”
Section: The Cr-ccsd[t] (Completely Renormalized Coupled-cluster Withmentioning
confidence: 99%